(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud Computing is one of the best compliment to information technology. Traditionally if we see the size of an instance or CPU time we will often have to be satisfied with computing approximate solutions but in the case of cloud computing we have to move one step ahead in the form of virtual machines. In cloud computing there are a numerous problems are present while scheduling requests from users. However in practice there is a need to be solving the issue efficiently even if not optimal. In this paper we have tried to obtain the solution based on existing heuristic approaches. Simulation results see the effectiveness of the approach